2014
DOI: 10.3390/ijms150712495
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor 1 Gene Polymorphism Is Associated with Susceptibility to Adverse Long-Term Allograft Outcomes in Non-Diabetic Kidney Transplant Recipients

Abstract: Although the genetic polymorphism of Stromal Cell-Derived Factor 1 (SDF-1) is associated with higher mortality of liver allograft recipients, the role of SDF-1 in the modulation of renal allograft outcomes is unclear. Between March 2000 and January 2008, we recruited 252 non-diabetic renal transplant recipients (RTRs). Baseline characteristics and blood chemistry were recorded. Genomic DNA extraction with polymerase chain reaction-restriction fragment length polymorphism was utilized to analyze the genetic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Both Lee et al [57] and Wang et al's. [58] teams proposed that AA/AG genotype and an allele of CXCL12 had adverse effects on the endpoint of allograft kidney transplantation. Therefore, genetic effects from donors should be carefully considered in order to select appropriate donors in kidney transplantation.…”
Section: Cxcl12 and Kidney Transplantationmentioning
confidence: 99%
“…Both Lee et al [57] and Wang et al's. [58] teams proposed that AA/AG genotype and an allele of CXCL12 had adverse effects on the endpoint of allograft kidney transplantation. Therefore, genetic effects from donors should be carefully considered in order to select appropriate donors in kidney transplantation.…”
Section: Cxcl12 and Kidney Transplantationmentioning
confidence: 99%
“…The CXCL12 rs1801157 polymorphism, comprising a guanine to adenine transition in the 3′ untranslated region (3′UTR), has been widely studied regarding its potential role in malignancy disorders, such as multiple myeloma , acute lymphoblastic leukemia , non‐Hodgkin's lymphoma , breast cancer , esophagogastric cancer , hepatocellular carcinoma and some others. There is also a number of studies documenting the association of this single nucleotide polymorphism (SNP) with the outcome of organ and hematopoietic stem cells transplantation . Our previous studies showed the association of the CXCL12‐3′A variant with the G‐CSF‐induced mobilization potential of CD34 progenitors from the bone marrow to the peripheral circulation in autologous transplant recipients as well as in healthy donors of allogeneic transplants.…”
Section: Discussionmentioning
confidence: 99%